2021
DOI: 10.1109/mgrs.2020.3043504
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Collective Agenda on AI for Earth Science Data Analysis

Abstract: This is the pre-acceptance version, to read the final version published in the Geoscience and Remote Sensing Magazine, please go to: 10.1109/MGRS.2020.3043504 In the last years we have witnessed the fields of geosciences and remote sensing and artificial intelligence to become closer. Thanks to both the massive availability of observational data, improved simulations, and algorithmic advances, these disciplines have found common objectives and challenges to advance the modeling and understanding of the Earth s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…In Bejiga et al [27], by using a multi-date, multi-site and multi-spectral dataset, it is observed that the use of domain adaptation for a problem with more than one source of domain shift (i.e., images of different spatial locations and acquired at different time periods) increases the level of challenge in unsupervised domain adaptation approaches, affecting their performance. For remote sensing applications, this implies that there is a need to use domain-specific knowledge [41] that would help to reduce some degree of domain shift, hence augmenting the unsupervised domain adaptation approaches. Most applications in computer vision assume the scene layout between images is comparable with the differences stemming from the spectral characteristics, for example, an image of the street taken in the morning and in the afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…In Bejiga et al [27], by using a multi-date, multi-site and multi-spectral dataset, it is observed that the use of domain adaptation for a problem with more than one source of domain shift (i.e., images of different spatial locations and acquired at different time periods) increases the level of challenge in unsupervised domain adaptation approaches, affecting their performance. For remote sensing applications, this implies that there is a need to use domain-specific knowledge [41] that would help to reduce some degree of domain shift, hence augmenting the unsupervised domain adaptation approaches. Most applications in computer vision assume the scene layout between images is comparable with the differences stemming from the spectral characteristics, for example, an image of the street taken in the morning and in the afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…During the demonstration of SyntEO, it could be shown how the approach can be utilised to establish fixed experiment environments and to generate highly adjustable dataset variants. Therewith, it was possible to make assumptions over the training process and model behaviour which is an important cornerstone towards explainable machine learning and interpretability of artificial intelligence, which is a current challenge in Earth observation and artificial intelligence [40]. The SyntEO approach starts a dialogue between machine and expert by using the ontology as a medium for exchange that both sides can interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, with the emergence of deep learning and especially its development in computer vision for image analysis [27], it became possible to extract complex spatio-temporal features from large amounts of remote sensing data. As a consequence, deep learning eventually established itself as an essential tool in Earth observation and gave new perspectives to geoscientific research [19,34,40,46].…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning in particular has led to a revolution in AI in recent years. Since taking off several years ago, deep learning in remote sensing has become a blooming research field ( Zhu et al, 2017 , Tuia et al, 2021 , Camps-Valls et al, 2021 ). Its huge potential in global urban mapping using EO data is ripe for discovery.…”
Section: Introductionmentioning
confidence: 99%